The marriage game [large type] : a novel of Queen Elizabeth I - Weir, Alison, 1951- (Thorndike Press Large Print, 2015)
"In this compelling novel of Tudor drama and suspense, acclaimed author Alison Weir brings to life one of England's most scandalous royal love affairs: the romance between the 'Virgin Queen' Elizabeth I and her courtier Lord Robert Dudley. Only twenty-five and newly crowned, Elizabeth vows to rule the country as both queen and king. But her counselors continually press her to form an advantageous marriage and produce an heir. Though none of the suitors have yet worked their way to her throne, the dashing--though married--Lord Robert lays claim to Elizabeth's heart. Their flagrant flirting, their unescorted outings, and the appointment of Lord Robert to Master of Horse inspire whispers through the court, and even rumors that Elizabeth has secretly given birth to Lord Robert's child. Events take a dark turn when Robert's wife is found dead. Universal shock is followed by accusations of murder. Despite the scandal, Elizabeth and Robert manage to navigate the choppy political, economic, and religious waters around them. But the greatest obstacle to marriage between the Queen and her true love may come not from outside forces, but from within. With intricate period detail and captivating prose, Alison Weir explores one of history's most provocative 'Did they or didn't they?' debates. The Marriage Game maneuvers through the alliances, duplicities, intrigue, and emotions of a woman intent on sovereignty--over her country and herself. Praise for Alison Weir A Dangerous Inheritance "A juicy mix of romance, drama and Tudor history. pure bliss for today's royal watchers."--Ladies' Home Journal "Highly compelling [with] plenty to keep readers enthralled."--Historical Novel Review Captive Queen "Should be savored. Weir wastes no time captivating her audience."--Seattle Post-Intelligencer "Stunning. As always, Weir renders the bona fide plot twists of her heroine's life with all the mastery of a thriller author, marrying historical fact with licentious fiction."--The Denver Post The Lady Elizabeth "Intrigue and maneuverings. Scandal. Schemers and innocents put to death. [This] history of Tudor England is an engrossing story. Weir marries conjecture with what is known about the life of Elizabeth I from childhood to coronation, and it makes for ripping good reading."--Milwaukee Journal Sentinel "A compelling, even irresistible, read."--Booklist (starred review)"--